2012
DOI: 10.1007/978-1-4614-2425-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Operational Analysis in the Launch Environment

Abstract: The launch environment is a challenging regime to work due to changing system dynamics, changing environmental loading, joint compression loads that cannot be easily applied on the ground, and control effects. Operational testing is one of the few feasible approaches to capture system level dynamics since ground testing cannot reproduce all of these conditions easily. However, the most successful applications of Operational Modal Testing involve systems with good stationarity and long data acquisition times. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The analysis of several recent data sets has shown that one effect (at least on the correlation-based processing approaches) is a "beating" or "blooming" phenomena which limits the amount of the correlation functions that can be used for processing. 30,35,39 Although the first low-lag points in the correlation functions are relatively unaffected, the higher-lag time data points are relatively useless for analysis. Figure 1 illustrates the beating phenomena as illustrated by a simple one DOF analytical model of a 10 Hz mode with 1% damping excited by random white noise using Newmark-Beta integration.…”
Section: Study Of Recursive Correlation and An Associated Convergencementioning
confidence: 99%
See 4 more Smart Citations
“…The analysis of several recent data sets has shown that one effect (at least on the correlation-based processing approaches) is a "beating" or "blooming" phenomena which limits the amount of the correlation functions that can be used for processing. 30,35,39 Although the first low-lag points in the correlation functions are relatively unaffected, the higher-lag time data points are relatively useless for analysis. Figure 1 illustrates the beating phenomena as illustrated by a simple one DOF analytical model of a 10 Hz mode with 1% damping excited by random white noise using Newmark-Beta integration.…”
Section: Study Of Recursive Correlation and An Associated Convergencementioning
confidence: 99%
“…Hence, this approach needs a convergence metric to allow the analyst to know when to stop performing additional correlations. 30 A metric was presented in reference [38] and will be repeated here. However the ongoing effort has discovered that there are numerical issues with the recursive correlation approach that need to be understood as validation of the technique is proving elusive.…”
Section: Previous Findingsmentioning
confidence: 99%
See 3 more Smart Citations